A QSPM Strategy to Control Inventory Turnover in Aerospace Industry - Putri, Cynthia Andansari; Dora, Yenny Maya (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study analyzes the current inventory management of PT. UTX and develops a data-driven control strategy by integrating internal and external strategic factors, addressing the aerospace industry’s unique high-dependency and certification requirements that are rarely explored in prior research. A key novelty of this research lies in the integration of the SWOT framework and the Quantitative Strategic Planning Matrix (QSPM) to design aerospace inventory strategies—an approach that has not been explicitly applied in this context before. Methodology: A sequential exploratory mixed methods approach was applied, starting with qualitative interviews and followed by quantitative strategic analyses to evaluate factors influencing inventory turnover Research Findings: PT. UTX maintains a solid planning system through MPS and leverages 3PL and bonded logistics centers, yet faces issues in digital integration, cross-functional coordination, and single-source supplier dependency. The analysis positions the company in a “grow and build” strategy, with backward integration identified as the most effective approach to enhance efficiency and supply chain resilience .Limitations: The study focuses on PT. UTX and relies on internal expert input, which may limit generalizability to other contexts. Contribution: This research advances supply chain strategy literature by integrating mixed methods with strategic tools, empirically validating backward integration and multi-sourcing as resilience strategies in high-certification industries like aerospace. Novelty: The study uniquely combines qualitative insights and quantitative models to design an inventory control framework, emphasizing backward integration and multi-sourcing to strengthen supply chain resilience.